An apposition‐like compound eye with a layered rhabdom in the small diving beetle Agabus japonicus (Coleoptera, Dytiscidae). (30th May 2014) - Jia, Lei‐Po; Liang, Ai‐Ping
ABSTRACT The fine structure of the compound eyes of the adult diving beetle Agabus japonicus is described with light, scanning, and transmission electron microscopy. The eye of A. japonicus is mango‐shaped and consists of about 985 ommatidia. Each ommatidium is composed of a corneal facet lens, an eucone type of crystalline cone, a fused layered rhabdom with a basal rhabdomere, seven retinula cells (including six distal cells and one basal cell), two primary pigment cells and an undetermined number of secondary pigment cells that are restricted to the distalmost region of the eye. A clear‐zone, separating dioptric apparatus from photoreceptive structures, is not developed and the eye thus resembles an apposition eye. The cross‐sectional areas of the rhabdoms are relatively large indicative of enhanced light‐sensitivity. The distal and central region of the rhabdom is layered with interdigitating microvilli suggesting polarization sensitivity. According to the features mentioned above, we suggest that 1) the eye, seemingly of the apposition type, occurs in a taxon for which the clear‐zone (superposition) eye is characteristic; 2) the eye possesses adaptations to function in a dim‐light environment; 3) the eye may be sensitive to underwater polarized light or linearly water‐reflected polarized light. J. Morphol. 275:1273–1283, 2014. © 2014 Wiley Periodicals, Inc.